Sodium fertilization increases termites and enhances decomposition in an Amazonian forest - Donoso Vargas, D. (2017)
Added Na was used to determine whether litter decomposition and associated fungal biomass and termites are limited by Na availability in a lowland tropical rainforest at Yasuni, Ecuador. This is a partial test of the "sodium ecosystem respiration" (SER) hypothesis that posits Na is critical for consumers but not plants, that Na shortfall is more likely on highly weathered soils inland from oceanic aerosols, and that this shortfall results in decreased decomposer activity. We fertilized 4 x 4 m plots twice a month for a year with quantities of Na comparable to those falling on a coastal tropical rainforest. Decomposition rates of four substrates were consistently higher on +NaCl plots by up to 70% for cellulose, and 78%, 68%, and 29% for three woods of increasing percentage lignin. The density of termite workers averaged 17-fold higher on +NaCl plots; fungal biomass failed to differ. After controlling for temperature and precipitation, which co-limit gross primay productivity (GPP) and ecosystem respiration (ER), these results suggest that Na shortfall is an agent enhancing the storage of coarse woody debris in inland tropical forests.